Menyorot Perjamuan Kudus kepada Anak sebagai Inisiasi dari Lensa Sosial Budaya - Rasid Rachman (KENOSIS: Jurnal Kajian Teologi, 2022)
Receiving Communion to children is a long conversation in some international churches. However, those conversations of about 100 years has not been finished yet in the context of the Protestant Churches in Indonesia. The reason for the delay is not only because this issue is a new discourse, but also the “concept” of worship in Indonesia is from and for adults only. Tracing of the ritual study in this paper brings the conversation of communion to children or paedocommunion to wider perspective. Paedocommunion is not only a matter of historical, biblical, or children's rights in worship, but also relates to the rite of initiation. Paedocommunion has to do with understanding one's initiation into adulthood. This initiation conversation does not only raise the issue of the rights of children who have been baptized and take communion in the Eucharist. In the perspective of anthropological and social initiation, paedocommunion begins with child baptism, and is related to catechism, confirmation, and the Holy Communion. The purpose of this paper is that the receiving communion to children should be investigated thoroughly as a sequence of initiation rites for ecclesiating someone. The closing of the paper is a discourse on integrating paedocommunion in initiation rites. AbstrakMenerimakan komuni kepada anak merupakan percakapan lama di beberapa gereja internasional. Namun, percakapan sekitar 100 tahun ini tak kunjung selesai dalam konteks Gereja-gereja Protestan di Indonesia. Penyebab keterlambatan itu bukan hanya karena isu ini merupakan wacana baru, tetapi juga “konsep” ibadah di Indonesia adalah dari dan untuk orang dewasa. Telusur studi ritus dalam makalah ini membawa percakapan komuni kepada anak atau paedocommunion kepada perspektif lain. Paedocommunion tidak hanya soal historisitas, biblis, atau hak anak dalam ibadah, tetapi juga kait mengait dengan ritus inisiasi. Paedocommunion harus disangkutkan dengan pemahaman inisiasi kedewasaan seseorang. Percakapan inisiasi ini tidak hanya mengangkat persoalan hak anak yang telah dibaptis dan mengambil komuni. Dalam perspektif inisiasi secara antropologis dan sosial, paedocommunion dimulai dari baptisan anak, dan kaitannya dengan katekisasi, sidi, dan bermuara pada perjamuan kudus. Tujuan makalah ini adalah bahwa menerimakan komuni kepada anak harus ditelisik secara menyeluruh sebagai urutan ritus inisiasi menggerejakan seseorang. Penutup makalah adalah wacana memadukan paedocommunion di dalam ritus inisiasi.